2022
DOI: 10.3390/app13010573
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Hidden Markov Models in Identifying Alterations in Movement Patterns during Biceps-Curl Weight-Lifting Exercise

Abstract: This paper presents a comparison of mathematical and cinematic motion analysis regarding the accuracy of the detection of alterations in the patterns of positional sequence during biceps-curl lifting exercise. Two different methods, one with and one without metric data from the environment, were used to identify the changes. Ten volunteers performed a standing biceps-curl exercise with additional loads. A smartphone recorded their movements in the sagittal plane, providing information on joints and barbell seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Thus, the novelty of the current study was the evidence that an HMM is also a suitable computerized method to analyse more complex movement (i.e., multi-joint or multi-segmental motions) than a single-joint action, as analysed previously by Peres et al [ 48 ]. Moreover, the current analysis demonstrated that HMMs can provide more accurate information on motion patterns than human visual observation, which was only speculated from the results of Peres et al [ 53 ].…”
Section: Discussionmentioning
confidence: 72%
“…Thus, the novelty of the current study was the evidence that an HMM is also a suitable computerized method to analyse more complex movement (i.e., multi-joint or multi-segmental motions) than a single-joint action, as analysed previously by Peres et al [ 48 ]. Moreover, the current analysis demonstrated that HMMs can provide more accurate information on motion patterns than human visual observation, which was only speculated from the results of Peres et al [ 53 ].…”
Section: Discussionmentioning
confidence: 72%